Qualitative marketing research : understanding consumer behaviour - Maison, Dominika (New York Routledge Taylor $Francis Group, 2019)
"This new edition of Qualitative Marketing Research seamlessly integrates theoretical foundations with practical applications in qualitative marketing research, positioning methodologies within the broader landscape of marketing strategy, managerial decision-making, and contemporary consumer psychology. The book offers an extensive examination of qualitative research approaches, beginning with established techniques like focus group interviews (FGI) and individual in-depth interviews (IDI), before exploring innovative ethnographic methods that reveal authentic consumer motivations, needs, values, and attitudes. Readers will gain profound insights into the psychological underpinnings of consumer behaviour, including cutting-edge understanding of unconscious and automatic cognitive processes that drive purchasing decisions. This thoroughly revised 2nd edition features an expanded chapter dedicated to digital research methodologies, covering online and video-based focus groups, social media analytics, mobile ethnography, and the revolutionary integration of artificial intelligence in consumer research. Distinguished by its practical orientation, the text incorporates diverse international case studies from market-leading organizations including PepsiCo, Unilever, Danone, Nestlé, Aviva, and Citibank, demonstrating how theoretical concepts translate into actionable insights across various industries and cultural contexts. This definitive work serves as indispensable reading for advanced undergraduate and postgraduate students specializing in marketing research, consumer behaviour, and consumer psychology. This book offers complementary online resources including comprehensive chapter-by-chapter PowerPoint presentations"-- Provided by publisher.
Keywords: Marketing research; Qualitative research